2005
DOI: 10.1158/0008-5472.can-04-3426
|View full text |Cite
|
Sign up to set email alerts
|

Kringle 5 of Human Plasminogen Induces Apoptosis of Endothelial and Tumor Cells through Surface-Expressed Glucose-Regulated Protein 78

Abstract: Kringle 5 (K5) of human plasminogen has been shown to inhibit angiogenesis by inducing the apoptosis of proliferating endothelial cells. Peptide regions around the lysine-binding pocket of K5 largely mediate these effects, particularly the peptide PRKLYDY, which we show to compete with K5 for the binding to endothelial cells. The cell surface binding site for K5 that mediates these effects has not been defined previously. Here, we report that glucose-regulated protein 78, exposed on cell surfaces of proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
216
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 227 publications
(234 citation statements)
references
References 35 publications
16
216
1
Order By: Relevance
“…7 Although K5 was hypothesized to be internalized into ECs, no experimental evidence has been presented. 6 We demonstrated here that ISM is efficiently internalized into ECs through clathrin-dependent endocytosis and internalization is essential for its antiangiogenic and proapoptotic function (Figure 1). The endocytosed ISM-GRP78 complex is targeted to mitochondria where ISM interacts with AACs on the inner membrane and blocks ADP/ATP exchange (Figures 4 and 5; Supplementary Figure S6).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…7 Although K5 was hypothesized to be internalized into ECs, no experimental evidence has been presented. 6 We demonstrated here that ISM is efficiently internalized into ECs through clathrin-dependent endocytosis and internalization is essential for its antiangiogenic and proapoptotic function (Figure 1). The endocytosed ISM-GRP78 complex is targeted to mitochondria where ISM interacts with AACs on the inner membrane and blocks ADP/ATP exchange (Figures 4 and 5; Supplementary Figure S6).…”
Section: Discussionmentioning
confidence: 79%
“…20 Similar to ISM, K5 also induced apoptosis in both ECs and cancer cells that present a high-level cell-surface GRP78. However, while K5 only induced significant apoptosis in cultured B16F10 melanoma cells under hypoxia, ISM induced B16F10 apoptosis under normaxia (Supplementary Figure S4; Davidson et al 6 ). Par-4 induces apoptosis both intracellularly and extracellularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that peptide regions around the lysine-binding pocket of K5 largely mediate its apoptosis-inducing action, and it plays a key role in the antiangiogenic and antitumor activity of K5. 17 These results indicate that recombinant K5 acts as an inhibitor of stress response pathway and leads to both endothelial and tumor cell apoptosis. 17 Various doses of rhK5 could induce apoptosis of LLC cells in normal culture condition, but it did not induce the apoptosis of B16F10 cells (unpublished data) at the same dose range.…”
Section: Discussionmentioning
confidence: 84%
“…16 Recent studies have suggested that recombinant K5 can induce apoptosis of proliferating endothelial cells involving enhanced activity of caspase-7 in stressed tumor cells. 17 Because of its high efficacy, cell type selectivity, and small molecular weight, K5 has considerable potential in the treatment of neovascular diseases including solid tumors. 14 In the present study, the therapeutic effect of radiotherapy combined with rhK5 is investigated in Lewis lung carcinoma (LLC) tumor model.…”
mentioning
confidence: 99%